Design and characterization of a thermooptic polymer switch based on directional coupler structure / Muhamad Arif Fahmi Mohd Husni - Mohd Husni, Muhamad Arif Fahmi (2011)
The thermo-optic switch proposed in this project is based on the principle of directional coupler structure to create an optical switching when the existence of heater on top of either one of waveguide. When sufficient heat is supply to the heater, it will disturb the propagation of wave in the waveguide. Hence, the switching between two waveguide will occur. Due to the increasing need of a smaller gadget, thermo-optic switch must be in smaller size. It also need to be low power consumption and with good efficiency. During the fabrication of the device, some errors may occur. Therefore fabrication tolerance analysis was conducted in order to evaluate the damage tolerance during fabrication. Error in fabrication tolerant must not affect the efficiency of the device. In the propose thermo-optic switch design, two 2x2µm PMMA waveguides were used as core with Teflon as cladding layer with thickness of 4µm, silica as a buffer layer with thickness of 10µm and silicon as a base that acting as a heat sink with thickness of 2µm. Heater is situated at the top of the waveguide. At the waveguide gap of 5µm and cladding thickness of 4µm from the buffer layer (2µm from top of waveguide), the coupling length of the device is 10616.44µm. When no heat applied, the directional coupler is in cross-state. Then at temperature of 26°C switching occur and the directional coupler is in the bar-state. Extinction ratio in the bar-state is 34.08dB. Fabrication tolerance of ±2% in the coupling length produce change in extinction ratio of about 23.77%